Electric power distribution handbook - Short, T. A. (Tom A.), 1966- (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'Preface In industrialized countries, distribution systems deliver electricity literally everywhere, taking power generated at many locations and delivering it to end users. Generation, transmission, and distribution--of these big three components of the electricity infrastructure, the distribution system gets the least attention. Yet, it is often the most critical component in terms of its effect on reliability and quality of service, cost of electricity, and aesthetic (mainly visual) impacts on society. Like much of the electric utility industry, several political, economic, and technical changes are pressuring the way distribution systems are built and operated. Deregulation has increased pressures on electric power utilities to cut costs and has focused emphasis on reliability and quality of electric service. The great fear of deregulation is that service will suffer because of cost cutting. Regulators and utility consumers are paying considerable attention to reliability and quality. Another change that is brewing is the introduction of distributed generation on the distribution system. Generators at the distribution level can cause problems (and have benefits if properly applied). New loads such as plug-in vehicles may be on the horizon. Customers are pressing for lower costs, better reliability, and less visual impact from utility distribution systems. Deregulation and technical changes increase the need by utility engineers for better information. This book helps fill some of those needs in the area of electric distribution systems. The first few chapters of the book focus on equipment-oriented information and applications such as choosing transformer connections, sizing and placing capacitors, and setting regulators'--
Includes bibliographical references and index.
Keywords: Electric power distribution -- Handbooks, manuals, etc